Effect of impact exercise on physical performance and cardiovascular risk factors - Vainionpää, Aki; Korpelainen, Raija; Kaikkonen, Hannu; Knip, Mikael; Leppäluoto, Juhani; Jämsä, Timo (Medicine and science in sports and exercise, 2007)
Impact exercise is known to be beneficial for bones, but information regarding its effects on other health aspects is scarce. The aim of this study was to assess the effects of high-impact exercise on physical performance and glucose and lipid profiles. We performed a 12-month, population-based, randomized controlled trial with 120 women (60 in the exercise group and 60 in the control group; ages 35-40 yr). The exercise regimen comprised supervised, progressive, high-impact exercises two to three times per week and an additional home program. Physical activity was continuously recorded using an accelerometer-based method and was analyzed as the daily number of impacts within five acceleration ranges between 0.3 and 9.2g (g = acceleration of gravity: 9.81 m x s(-2)). The changes in physical performance and in glucose and lipid profiles were determined. Thirty-nine women in the exercise group and 41 women in the control group completed the study. Maximal oxygen uptake (6.2 vs 3.1 mL x kg(-1) x min(-1); P = 0.008) and countermovement (2.3 vs -0.3 cm; P < 0.001) and static (1.4 vs -0.3 cm; P = 0.004) jump heights increased significantly more in the exercise group than in the control group. Exercise training also decreased waist (-1.1 vs 0.9 cm; P = 0.048) and hip circumference (-1.0 vs 1.1 cm; P = 0.037). Total cholesterol and LDL cholesterol decreased significantly more in women, with the highest number of impacts compared with the lowest quartile at intensities exceeding 1.1g, with differences being up to -0.5 mM (P = 0.005). Additionally, poor baseline values predicted greater exercise effects. The moderate-intensity exercise regimen, initially targeted at weight-bearing bones, improved cardiorespiratory fitness, speed-strength, and lipid profiles. In addition to bone health, impact exercise may be recommended for prevention of cardiovascular diseases.